ASSESSMENT OF THE POSSIBILITY OF REDUCING THE NEGATIVE IMPACT ON THE ENVIRONMENT OF THE SECOND AND THIRD STAGES OF WATER TREATMENT IN REVERSE OSMOSIS SYSTEMS - KARPENKO, MARGARYTA; RADOVENCHYK, VYACHESLAV (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Reverse osmosis systems of low and medium productivity include up to 7-9 stages of water treatment to bring its quality to drinking quality. At the same time, the main component of such systems is the membrane, and the first three stages of treatment of the incoming water are designed to protect it from damage and extend the service life. The period of exhaustion of the cartridge resource is 3-6 months, after which the cartridges replenish the volume of solid household waste, increasing the burden on the environment, the content of microplastics in its components, irreversibly losing valuable natural raw materials. The cartridge of the first stage of pre-membrane water treatment is a monolithic polypropylene block and can be successfully regenerated by chemical methods for reuse. Cartridges of the second stage are mainly represented by carbon-containing materials, the regeneration of which is economically impractical today, so such cartridges can be disposed of by thermal methods. Another way to solve the problem can be the manufacture of cartridge housings dismountable, which will allow after the resource is exhausted at service enterprises to replace the contents of the cartridge and restore its properties. Things are much worse with cartridges of the third stage of water treatment. Even within the model range of one manufacturer, materials with different properties are often used, which prevents not only their regeneration, but also makes effective disposal impossible. The problem of using substances capable of transforming at high temperatures (silver blocks) or complex cartridges containing several (three to five) materials with different properties at the same time deepens the problem even more. In this case, the organization of replacing the used cartridges with new ones and returning the used ones to the manufacturing enterprises for disposal in the conditions of their industrial production seems to be the most likely.